Vita`s modernism: the green Sackville-West - Herndon Marshall, Ann (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The reservations of Virginia Woolf about Vita Sackville-West`s fiction have long dominated her legacy. What Marina McKay calls the "decisive historicist turn in modernist studies" continues to exclude Vita because she is written off as a reactionary, yet her garden writing challenges pastoral ideals. As a garden writer, she undermines beliefs about women and the natural world.
Keywords: anthropocentrism; homocentrism; ecocriticism; feminism and gardening; garden writing; modernism; pastoral